Ensuring the Republic of Kazakhstan for ways to improve the stability of budgetary planning of the budget system . - Жумағалиев, Е. Б. (Journal of Economic Research & Business Administration, 2015)
The budget is an important socio - economic process of production , It plays a role in the political, economic , social development It is a tool . -adamdardıñ budget request swbɴektïvti No, he has expanded the functions of the state and the processing requirements defined by the required objectivity.